Respuesta :

Answer:

Please check the explanation!

Step-by-step explanation:

Given the equation

[tex]f\left(x\right)=-2|x+1|-1[/tex]

As some of the absolute rules are:

  • [tex]\left|a\right|=a,\:a\ge 0[/tex]
  • [tex]\:|-a|=a,\:\quad \:a>0[/tex]

NOW, let us solve!

Let us substitute all the table values

Putting x = -4

[tex]y=-2\left|-4+1\right|-1[/tex]        ∵[tex]\mathrm{Apply\:absolute\:rule}:\quad \left|a\right|=a,\:a\ge 0[/tex]

[tex]y=-6-1[/tex]

[tex]y=-7[/tex]

So, when x = -4, then y = -7

Putting x = -3

[tex]y=-2|-3+1|-1\:[/tex]

[tex]y=-4-1[/tex]

[tex]y=-5[/tex]

when x = -3, then y = -5

Putting x = -2

[tex]y=-2\left|-2+1\right|-1[/tex]

[tex]y=-2-1[/tex]

[tex]y=-3[/tex]

when x = -2, then y = -3

Putting x = -1

[tex]y=-2\left|-1+1\right|-1[/tex]

[tex]y=-0-1[/tex]

[tex]y=-1[/tex]

when x = -1, then y = -1

Putting x = 0

[tex]y=-2\left|0+1\right|-1[/tex]

[tex]y=-2-1[/tex]

[tex]y=-3[/tex]

when x = 0, then y = -3

Putting x = 1

[tex]y=-2\left|1+1\right|-1[/tex]

[tex]y=-4-1[/tex]

[tex]y=-5[/tex]

when x = 1, then y = -5

The graph is also attached below.

Ver imagen absor201
ACCESS MORE